Mecanismos envolvidos no efeito antioxidante do disseleneto de difenila no dano oxidativo causado pela exposição à fumaça do cigarro em ratos jovens - Luchese, Cristiane (2009)
Cigarette smoking is a complex mixture of many constituents identified, among them reactive substances (reactive oxygen and nitrogen species), which are capable of initiating or promoting oxidative damage. Lungs and brain are affected by cigarette smoke exposure. Exposure to cigarette smoke is related to development of diseases in children and adults. However, children are more susceptible than adults to damage caused by cigarette smoke. Thus, the use of antioxidants is a good alternative to protect tissues of oxidative damage caused by cigarette smoke exposure. Diphenyl diselenide [(PhSe)2] is an organoselenium compound that presents pharmacological effects, among them the antioxidant effect. Nevertheless, the mechanism involved in antioxidant effect of (PhSe)2 was not been elucidated. Therefore, this study was performed to study the effects of cigarette smoke passive exposure in lungs and brain of rat pups in two experimental protocols of oxidative stress. Moreover, the antioxidant effect of (PhSe)2 in these experimental protocols was studied. Besides, the mechanisms involved in the antioxidant effect of (PhSe)2 were investigated. Rat pups that were exposed to two experimental protocols were used. In a first experimental protocol (P1), the effect of exposure to one, two and three cigarettes during the first, second and third weeks of live, respectively, was studied. In a second experimental protocol (P2), the effect of exposure to four, five and six cigarettes during the first, second and third weeks of life, respectively, was carried out. The duration of each exposure was 15 min. Animals were exposed to cigarette smoke during 20 days (3 weeks). Immediately before each exposure, animals that were treated with (PhSe)2 received daily an oral dose of 0.5 mg/kg. At the end of the experimental exposure period (3 weeks), rat pups were euthanized, and lungs and brain were removed for analyses of lipid peroxidation, enzymatic antioxidant defenses (superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), glutathione peroxidase (GPx), glutathione S-transferase (GST) activities) and non-enzymatic defenses (non-protein thiols (NPSH) and ascorbic acid levels). Rat pups were daily weighed, before each exposure. The weight of animals was not changed after cigarette smoke exposure neither to P1 nor to P2. In both experimental protocols, animals that were exposed to cigarette smoke showed an increase in lipid peroxidation in lungs. In brain, an increase in thiobarbituric acid reactive species (TBARS) was observed only in P2. Levels of non-enzymatic antioxidant defenses decreased in lungs of animals exposed to P1 and P2. In brain, exposure to P1 increased ascorbic acid levels and exposure to P2 reduced NPSH and ascorbic acid levels. Enzymatic antioxidant defenses changed in P2 in lungs of rat pups. In brain, the activity of CAT was reduced after exposure to P1, while SOD and CAT activities were decreased after exposure to P2. Treatment with (PhSe)2 restored the oxidative damage caused by cigarette smoke exposure in lungs and brain of rat pups. Moreover, NPSH levels, ascorbic acid content and GST activity showed an increase per se in lungs of animals treated with (PhSe)2. The mechanisms involved in antioxidant effect of (PhSe)2 (1 - 50 μM) were studied. To this end, dehydroascorbate (DHA) reductase and GST activities were determined. (PhSe)2 at concentration of 5 μM demonstrated DHA reductase and GST-like activities. Furthermore, the scavenger effect of 2,2 -diphenyl-1-picrylhydrazyl (DPPH ) radical and 2,2 -azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS +) radicals, and the protection of Fe2+ autooxidation were studied. However, the compound had no scavenger effect or protected Fe2+ autooxidation, discarding that these mechanisms are involved in the antioxidant effect of (PhSe)2. Synthesis of glutathione (GSH) was also studied as a possible mechanism involved in antioxidant effect of (PhSe)2. For this, buthionine sulfoximine (BSO), a substance that inhibits γ-glutamilcystheine synthase activity, an enzyme involved in the synthesis of GSH was used. BSO blocked the protective effect of (PhSe)2 in reducing NPSH levels caused by cigarette smoke passive exposure in lungs and liver of rat pups. In this study it was concluded that (PhSe)2 had antioxidant effect by different mechanisms. The action of (PhSe)2 to increase NPSH and ascorbic acid levels, and GST activity is one of mechanisms of the antioxidant effect of this compound. (PhSe)2 presented DHA reductase and GST-like activities, demonstrating a new mechanism of antioxidant effect of the compound. Furthermore, the synthesis of GSH is involved in the antioxidant role of (PhSe)2, since blocking the synthesis of GSH, presented the antioxidant effect of this compound.